Knowledge of mothers on diaper dermatitis management and associated factors in Ethiopia - Atoma Negera; Midekso Sento; Gemechu Tola (Scientific Reports)
Abstract Diaper dermatitis is an inflammatory reactions of the skin under a diaper due to prolonged skin contact with irritants (urine and faeces), seborrhoea, allergic reaction, fungal (candida), and bacterial infections. It is more common in children aged 1–24 months, with the majority of instances occurring in newborns younger than one year. Over half of newborns suffer from the case at least once throughout their diaper-wearing phase. In low- and middle-income countries like Ethiopia, there is a lack of published data regarding the degree of parental knowledge of diaper dermatitis, its management, and the risk factors associated with the disease. Moreover, the topic receives little to no attention. Therefore, this study aims to assess the mothers’ knowledge of diaper dermatitis and the risk factors linked with the disease. Data was collected from 396 mothers who came for immunization services from August 01 to September 01, 2024, consecutively. The data was cleaned, checked for completeness manually, and entered into SPSS version 26 for analysis. A binary multivariable logistic regression was used to analyze the association between the independent and the outcome variables. Variables with a p-value < 0.05 were considered statistically significant, and an adjusted odds ratio with a 95% confidence interval was reported. The study findings revealed that 84.6% of mothers had self-reported good knowledge of DD and its management, and their main source of information is family members and relatives (35.4%). Nearly two-thirds (65.4%) of children experienced DD, and only 23.6% sought healthcare. Over one-third (37.1%) of mothers used Vaseline to treat DD at home, followed by baby powder (35.1%). The majority (83.6%) of mothers uses disposable diapers only, and 84.8% change 0–2 times per day. The output of logistic regression shows that being a 7–12 month-old child (aOR = 4.03; 95% Cl (1.41–11.50)), being a male child (aOR = 2.16; 95% Cl (1.14–4.06)), and being firstborn (aOR = 5.95; 95% Cl (1.39, 25.53)) variables had a significant association with knowledge of mothers. The study found that although the majority of mothers have self-reported good knowledge, a significant number of them have no awareness of the diapering practice, how to treat DD, when to seek medical attention, and how to take care of their skin after a bowel movement. Therefore, we suggest a structured teaching program to increase mothers’ understanding of DD, including its prevention and management.